UPAYA MENERAPKAN METODE ARTIKULASI UNTUK MENGATASI KESULITAN MEMBACA LANCAR - Putra, Dipa Satria (JURNAL PENA EDUKASI, 2018)
Abstract: Classroom action research in general aims to improve the quality of learning for VII grade students of SMP Negeri 1 Sei Kepayang distrcit Asahan. specifically aimed at: (1) Efforts to Implement Articulation Methods to Overcome Current Reading Difficulties with Basic Material Impressive Experiences in Indonesian Language Subjects for Grade VII Students of Sei Kepayang 1 Junior High School District. Asahan TP. 2017/2018; (2) Describe the management of Indonesian language learning by teachers. This classroom action research is carried out in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. Classroom action research was carried out in class VII of SMP Negeri 1 Sei Kepayang distrcit Asahan which numbered 31 students. The subjects of this study were Grade VII Indonesian Language Teachers and VII grade students of SMP Negeri 1 Sei Kepayang distrcit Asahan data is collected through observation, interviews, tests, and documentation studies. Keyword: Articulation Method, Difficulty Reading Smoothly Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas VII SMP Negeri 1 Sei Kepayang kab. Asahan. secara khusus bertujuan untuk: (1) Upaya Menerapkan Metode Artikulasi Untuk Mengatasi Kesulitan Membaca Lancar Dengan Materi Pokok Pengalaman Mengesankan Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas VII SMPN 1 Sei Kepayang Kab. Asahan TP. 2017/2018; (2) Mendeskripsikan pengelolaan pembelajaran Bahasa Indonesia oleh guru. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan dikelas VII SMPN 1 Sei Kepayang kab. Asahan yang berjumlah 31 orang siswa. Subjek penelitian ini adalah guru Pelajaran Bahasa Indonesia kelas VII dan siswa kelas VII SMPN 1 Sei Kepayang Kab. Asahan, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata kunci: Metode Artikulasi, Kesulitan Membaca Lancar